TANGGAPAN PENGUNJUNG PADA DAYA TARIK WISATA DI TANGSI BELANDA KECAMATAN MEMPURA KABUPATEN SIAK - Larashati, Shahira; Martina, Elti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research aims to analyze visitor responses to historical tourist attractions in Dutch Tangsi, Mempura District, Siak Regency. The research used quantitative descriptive methods with data obtained through questionnaires filled out by 97 respondents. Data were analyzed using a Likert scale approach to measure visitors' perceptions of aspects of Natural Tourism Attraction, Building Tourism Attraction, Cultural Tourism Attraction and Social Tourism Attraction. The research results show that the majority of visitors gave positive responses, with the average value being in the Agree to Strongly Agree category. The most interesting aspects include the architectural beauty of the building, historical value, and natural scenery around the location. However, several shortcomings were identified, such as a lack of adequate historical information, a lack of educational facilities, and the absence of competent tour guides. In conclusion, Dutch Tangsi has great potential to be developed as an interesting and educational historical tourism destination. Improvements in aspects of services and facilities are very necessary to improve the tourist experience. It is hoped that the results of this research can be a guide for managers and local governments in maximizing the potential of Dutch Tangsi as a leading tourist destination in Siak Regency. Keywords: Visitor Response, Tourist Attraction, Historical Tourism, Dutch Tangsi, Siak Regency.